El Llibre místic de Sant Romà de les Bons (Andorra) (Biblioteca de l'Abadia de Montserrat, ms. 72) - Altés i Aguiló, Francesc Xavier (Miscel·lània litúrgica catalana, 2005)
The manuscript 72 from the Montserrat Abbey Library is a Liber Misticus that contains some importants texts from the missal, the breviary and the ritual compiled in a single volume. It dates from the mid-12th century and comes from the small chapel in Sant Romà de les Bons, Andorra. Its importance lies, among other aspects, in the fact of being the only fully preserved copy of this kind of liturgical book from a Catalan church and, since it was written at the Urgell cathedral, it also serves to better know the liturgical texts used in this Pyrenees bishopric in that century, of wich there is unfortunately almost no other liturgical evidence.